Application of Sport Education Models in Basic Movement Skills Passing Under the Volume Ball Game - Hendri Munar; Ceppy Aditya; Mudjihartono Mudjihartono; Dian Budiana (Universitas Pendidikan Indonesia (UPI), 2021)
The main objective of this research is to determine the extent of implementation of sports education model on the basic movement skills of forearm pass in volleyball. The research method used was an experimental method with a pre-test and post-test control group research design. The subjects of this study were students of class VII SMPN 1 Plered Cirebon with total sample of 22 students divided into two groups, namely the experimental group and the control group. The research instrument used was a modified forearm pass accuracy test from the Braddy Volley Ball Test and documentation. The final results of this research, we could see there is an effect of the sportsÂ education model on improving learning outcome skills of forearm pass in volleyball game as the author has described above. The mean of the sports education model group has a value of 15.36 with a final score of 21.00 having a percentage difference of 70%. While the average value of the control group was 16.36 and the final score was 17.82 with a percentage difference of 59.4%. The t value is smaller than the t table, therefore the hypothesis is accepted. Thus it can be concluded that there is a significant effect on the sports education model group on the improvement of forearm pass in volleyball. Thus it can be concluded that there is a significant effect in the sports education group on the improvement of volleyball forearm pass skills.